Implementation of Learning Cycle 7E Assisted by Digital Worksheet to Improve Students’ Learning Outcomes and Motivation - Yunike Valeryn Wahyu; Herunata; Silviani (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study aims to enhance student learning outcomes and motivation in the Mol Concept material by applying the Learning Cycle 7E learning model, assisted by digital worksheet, integrated with Liveworksheets. The study was conducted as classroom action research in Class X-E SMAN 2 Malang over two cycles. The methods used include pre-cycle, cycle I, and cycle II with test and observation instruments. The results showed an increase in student learning outcomes, from an average score of 67.31 in the pre-cycle to 76.81 in cycle II, as well as an increase in learning motivation in five main aspects. The use of the Learning Cycle 7E model and interactive digital media can encourage student involvement, enhance learning outcomes, and foster a more engaging and participatory learning environment.